How Bacterial Pathogens Eat Host Lipids: Implications for the Development of Fatty Acid Synthesis Therapeutics - Yao, Jiangwei (J Biol Chem, 2015)
Bacterial type II fatty acid synthesis (FASII) is a target for the development of novel therapeutics. Bacteria incorporate extracellular fatty acids into membrane lipids, raising the question of whether pathogens use host fatty acids to bypass FASII and defeat FASII therapeutics. Some pathogens suppress FASII when exogenous fatty acids are present to bypass FASII therapeutics. FASII inhibition cannot be bypassed in many bacteria because essential fatty acids cannot be obtained from the host. FASII antibiotics may not be effective against all bacteria, but a broad spectrum of Gram-negative and -positive pathogens can be effectively treated with FASII inhibitors.